2017
DOI: 10.1080/17503280.2017.1340796
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality witness: exploring the ethics of mediated presence

Abstract: The notion of immersive witness underpins much of the exploration of VR by journalists and humanitarian organisations. Immersive witness links the experience of VR with a moral attitude of responsibility for distant others. In accounts of media witness, the ability of the media to sustain an experience of presence has played an important, albeit often implicit, role linking the spectator spatially and temporally to distant suffering. However, the concept of media witness has to date assumed that the media repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 24 publications
1
71
0
10
Order By: Relevance
“…Observation is characterised as passiveness since the user does not assume a role in the story, and the omniscient perspective refers to being a tourist, when the initial task of the user is to direct attention according to the VO. In fact, studies have shown that the majority of IJ projects tend to utilise two or more POVs (Bevan et al 2019;de la Peña et al 2010;McRoberts 2018;Nash 2018). Therefore, the shift in perspectives can confuse the user when differentiating between the emotions represented in the story and the emotional responses felt by the user (Sánchez Laws 2017).…”
Section: Emotional Engagement In Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…Observation is characterised as passiveness since the user does not assume a role in the story, and the omniscient perspective refers to being a tourist, when the initial task of the user is to direct attention according to the VO. In fact, studies have shown that the majority of IJ projects tend to utilise two or more POVs (Bevan et al 2019;de la Peña et al 2010;McRoberts 2018;Nash 2018). Therefore, the shift in perspectives can confuse the user when differentiating between the emotions represented in the story and the emotional responses felt by the user (Sánchez Laws 2017).…”
Section: Emotional Engagement In Vrmentioning
confidence: 99%
“…The purpose of VR is to simulate experiences for the audience while serving as a communicative medium. Nash (2018) argued that, despite the prominence of VR technology's ability to enhance empathy toward the characters, it may draw more attention to the user and the quality of the experience. Concerns about empathy being produced by using dramatic and/or even traumatic media content to create more perceptual, realistic experiences have initiated an ethical discussion concerning IJ (de la Peña et al 2010; Kool 2016; Sánchez Laws 2017).…”
Section: Emotional Engagement In Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…Another problem is that the proximity with a subject can be uncanny, so emotional scenes can end up being awkward or even disturbing. This happens in <Waves of Grace 2015>, where main character Decontee Davis is crying and the viewer is placed extremely close to her (see Figure 5), but is ultimately unable to console her, generating an uncanny experience [5]. Other inconsistencies can occur in the moment of recording itself.…”
Section: The Reality Of Humanitarian Vr: New Variations In the Gmentioning
confidence: 99%
“…There is a corresponding groundswell of research into VRNF, particularly into ways that affordances of VR -"presence" [e.g. 11,9,4,1,13], "immersion" [e.g. 5, 10] and, perhaps, "empathy" [e.g.…”
Section: Background and Related Workmentioning
confidence: 99%